ANALYSIS OF THE BEST PRACTICES OF IMPLEMENTING LEAN PROJECT AND PROGRAM MANAGEMENT TECHNOLOGIES IN RUSSIA - T. D. Gilmanov; T. A. Sayfullin; Yu. E. Yushchenko; E. A. Khalimon (Вестник университета)
This article considers the principles and tools of lean management. The paper gives practical examples of the implementation of the concept of lean production in large Russian organizations, in state and municipal institutions. The analysis showed that there are many opportunities for improving operational and project activities that justify the introduction of a lean approach in organizations. The problems in understanding the need for lean production arise since people are generally reluctant to change established processes, but positive follow-up examples contribute to the success of implementing lean management and help in developing adequate development strategies for companies and government agencies.